Development of a Multiplex PCR Platform for the Rapid Detection of Bacteria, Antibiotic Resistance, and Candida in Human Blood Samples - Liotti, Flora Marzia; Posteraro, Brunella; Mannu, Franca; Carta, Franco; Pantaleo, Antonella; De Angelis, Giulia; Menchinelli, Giulia; Spanu, Teresa; Fiori, Pier Luigi; Turrini, Francesco; Sanguinetti, Maurizio (Frontiers in Cellular and Infection Microbiology, 2019)
The diagnosis of bloodstream infections (BSIs) still relies on blood culture (BC), but low turnaround times may hinder the early initiation of an appropriate antimicrobial therapy, thus increasing the risk of infection-related death. We describe a direct and rapid multiplex PCR-based assay capable of detecting and identifying 16 bacterial and four Candida species, as well as three antibiotic-resistance determinants, in uncultured samples. Using whole-blood samples spiked with organisms at low densities, we found that the MicrobScan assay had a mean limit of detection of 15.1 ± 3.3 CFU of bacteria/Candida per ml of blood. When applied to positive BC samples, the assay allowed the sensitive and specific detection of BSI organisms, including blaKPC-, mecA-, or vanA/vanB-positive organisms. We evaluated the assay using prospectively collected blood samples from patients with suspected BSIs. The sensitivity and specificity were 86.6% and 97.0%, respectively, among patients with positive BCs for the organisms targeted by the assay or patients fulfilling the criteria for infection. The mean times to positive or negative assay results were 5.3 ± 0.2 h and 5.1 ± 0.1 h, respectively. Fifteen of 20 patients with MicrobScan assay-positive/BC-negative samples were receiving antimicrobial therapy. In conclusion, the MicrobScan assay is well suited to complement current diagnostic methods for BSIs.